Idealtheorie in Hadamard Algebren - Zohner, Jochen; Justus Liebig University Giessen (My University, 2013)
Gegenstand dieser Dissertation ist die Untersuchung von Räumen holomorpher Funktionen mit Hadamard-Multiplikation. Ein neuer, sehr einfacher Beweis des Hadamardschen Multiplikationssatzes wird angegeben, der sich komplexer Borel-Maße bedient. Diese Methode wird dann verwendet, um den Dualraum des Raums H(G), der auf einem Gebiet G holomorphen Funktionen, mit Hilfe des Hadamard-Produkts darzustellen.Es werden ferner Räume maximaler Ideale in Hadamard-Algebren und Algebren stetiger Funktionen untersucht. Dazu werden einige Eigenschaften der darauf eingeführten Hull-Kernel-Topologie bewiesen, und Kriterien für Homöomorphien unter diesen Räumen angegeben. Diese führen zu einer Bestimmung der Anzahl der maximalen Ideale in Hadamard Algebren, und zu einem Kriterium für Ring-Isomorphien unter den Hadamard-Algebren. Im Falle mehrfach zusammenhängender Gebiete erfolgt eine genauere Bestimmung des Raums der maximalen Ideale.

The topic of this thesis is the investigation of algebras of holomorphic functions with Hadamard multiplication.A new most simple proof of Hadamards multiplication theorem is given by means of complex Borel measures. This method is afterwards used to state a representation theorem for the dualspace of H(G) (the space of analytic functions on a given domain) using the Hadamard product. The space of maximal ideals will be investigated on Hadamard algebras as well as on algebras of continous functions. By endowing these spaces with the hull-kernel-topology some properties and homeomorphy criteons will be given. This leads to determining the number of maximal ideals in Hadamard algebras as well as an isometry criterion on Hadamard algebras. In the case of multiply connected domains, a more detailed investigation of the structure of the space of maximal ideals is provided.
Ideals in algebras of holomorphic functions with Hadamard multiplication
Keywords: Hull-Kernel-Topologie; Stone-Czech-Kompaktifizierung; Hadamard Produkt; Maximale Ideale; Hull-Kernel-Topology; Stone-Cech-Compactification; Hadamard Product; Maximal Ideals; ddc:510